Alterações hematológicas em cães e gatos sob estresse - Laurino, Felipe [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The leukocyte count interpretation on the blood helps on understanding about the possible dysfunction showed by the animal. In general, an abnormal leukogram allows the identification of pathological process. A lot of events lead to an increase in the number of neutrophils, among then, inflammatory process, infection and stress. Dependent on the stress mediator that the animal is submited, the leukocyte alteration will be different. Is important to know how the stress acts on the animal organism, changing the hematological parameters, in order to avoid mistakes on diseases‟ diagnosis. It‟s known that after a stress situation, it‟s expected that stress leukogram appears on the hemogram of the animal. However there are different kinds of stress with different responses. It‟s believed that when the animal is under an acute stress situation, a clinical picture of physiologic leukocytosis occurs which is mediated by the epinephrine. This is characterized by neutrophilia, lymphocytosis, monocytosis and eosinofilia. The physiologic leukocytosis is a transient alteration in the leukogram that occurs within minutes of the stimulus and due to fleeting effect of catecolamines it resolves within 20 to 30 minutes. However, if the animal is under chronicle stress, as solitude, it „s expected to find the stress leukogram on the leukogram, that can be noted especially in dogs. The stress leukogram is characterized by leukocytosis, neutrophilia, lymphopenia, monocytosis and eosinopenia. This kind of stress is induced by the glucocorticoids. It´s important to understand that stress leukogram takes time to occur. The variation on time depends on the animal species, although, in general, the glucocorticoides have a peak effects among 4 to 8 hours, which can last from 24 hours to 2 or 3 days

A interpretação das contagens de leucócitos do sangue auxilia na compreensão sobre as possíveis disfunções apresentadas pelo animal. Em geral, um leucograma anormal permite a identificação de processos patológicos. Uma série de eventos leva ao aumento do número de neutrófilos, dentre eles processos inflamatórios, infecciosos e o estresse. Dependendo do mediador de estresse que o animal está submetido, as alterações leucocitárias serão diferentes. É importante conhecer como o estresse age no organismo animal, modificando os parâmetros hematológicos, para evitar erros no diagnóstico de doenças. Sabe-se que após situações de estresse, espera-se que o leucograma de estresse apareça no hemograma do animal. Porém existem diferentes tipos de estresse, e, portanto, com diferentes respostas. Acredita-se que quando o animal está sob uma situação de estresse agudo, ocorrerá um quadro de leucocitose fisiológica, que é mediada pelas catecolaminas. Este é caracterizado por neutrofilia, linfocitose, monocitose e eosinofilia. A leucocitose fisiológica é uma alteração transitória no leucograma que ocorre com minutos do estímulo que, devido ao efeito fugaz das catecolaminas, dura em torno de 20 a 30 minutos. Porém, se o animal estiver sob estresse crônico, como solidão, espera-se encontrar no hemograma o leucograma de estresse, que poderá ser notado especialmente em cães. O leucograma de estresse é caracterizado por leucocitose, neutrofilia, linfopenia, monocitose e eosinopenia. Esse tipo de estresse é mediado pelos glicocorticóides. É importante entender que o leucograma de estresse leva tempo até aparecer. Há variações do tempo dependendo da espécie animal, porém, em geral, os glicocorticóides geram efeitos num pico de 4 a 8 horas, podendo durar de 24 horas até 2 a 3 dias
Keywords: Patologia clinica veterinaria